The clinical role of stool test (HpSA) in noninvasive diagnosis of Helicobacter pylori infection - Dino VAİRA,; Chiara Ricci,; Carmela ACCİARDİ,; Luigi Gatta,; Sonia BERARDİ,; Mario MİGLİOLİ, (Turkish Journal of Gastroenterology, 2019)
-